PEMARKAH RELASI PELESAPAN: STUDI PADA KARANGAN SISWA SEKOLAH MENENGAH PERTAMA - Wahid, Abdul; Syamsuri, Andi Sukri; Latief, Syekh Adiwijaya; Hasrianti, Andi (Universitas Negeri Makassar, 2024)
This study aims to identify the form of the use of dissipation as a marker of inter-propositional relations in junior high school students' essays. This study was designed using a qualitative research approach. 94 grade VIII students of SMP Negeri 1 Balikpapan were involved as research subjects in this study. The data in this study were collected using the 'seeing method' after the research subjects were given essay writing assignments to obtain documented data sources. Analysis of the research data consisted of three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are three types of omissions that are used as a means of linking one proposition to another in the research subject's essay, namely noun omission, verb omission, and propositional omission. Among the three categories, noun escape is more dominantly used by research subjects as a marker of relations between propositions than verb escape and proposition escape. This study also shows that research subjects tend to use structural and situational forms of disengagement rather than textual deletion, so that the relationship between propositions becomes disrupted. The findings of this study make an important contribution for language teachers to optimize learning and training in writing skills in classrooms.